PERTUNJUKAN SENDRATARI BAHOELA DAN KINI DALAM ACARA HORAS SAMOSIR FIESTA DI KABUPATEN SAMOSIR - MALAU, TRI MEYANI (Grenek: Jurnal Seni Musik, 2017)
The Bahoela and Today Sendratari Show at Horas Samosir Fiesta Event inSamosir Regency. Faculty of Arts and Languages. State University of Medan.2015. This research is aimed to know how the Bahoela and Today SendratariShow that will be held and the way of the event management from the beginninguntil the end is. In the discussion of this research, the researcher used relatedtheory to the topic of writing, such as theory of show, theory of sendratari andtheory of management. The research methodology used in this research wasdescriptive qualitative. To complete the data in this research, the researcherconducted a field observation, videos, interviewing and documentation. Thepopulation in this research was the whole involved committee, the performers andthe audiences. After all the data were collected, they were analysed then toanswer all the researcher™s questions. The data analysis was done by usingqualitative data technique which was described in phases in writing form. Afterthe analysis was done, it was found that the event management in order to makethe event run well, it was started form planning, determining the structure,preparing, conducting, making a responsibility report, evaluating the result,effects, redeveloping/replanning and the show presented music, drama and dancewhich told about occurrences in Bahoela Era and Today.